O ATENDIMENTO PÚBLICO EM HIV/AIDS NA CIDADE DE PONTA GROSSA – PR E A VISÃO DAS EQUIPES MULTIDISCIPLINARES SOBRE A UTILIZAÇÃO DA POLÍTICA NACIONAL DE HUMANIZAÇÃO NO GERENCIAMENTO DA EPIDEMIA - Wisniewski, Marcelo (2015)
Since the advent of AIDS in the 1980’s, much has been discussed about this syndrome. Either by strands designated as 'scientific' or not, the matter raised polemics, controversies, but also caused to science to put on demand urgent studies on the treatment of this disease. In Brazil, the arrival of innovative antiretroviral therapies from the second half of the 1990’s as well as the requirement for free distribution by the public health system, contributed undoubtedly to increase longevity and quality of life of people with HIV. Overcome this phase, the epidemic maintains its trajectory and other demands, among them, adherence to drug therapies, were outlined as mandatory elements for the successful treatment of this syndrome. In this study, it was intended to historically rescue the deployment of public services care for HIV / AIDS in Ponta Grossa - PR, from the point of view of multidisciplinary teams involved. Moreover, it was emphasized the historical trajectory of the management of these patients during the arrival of the National Humanization Policy (PNH). And how these professionals involved have assimilated this police of the Unified Health System to develop promotion strategies for adherence to antiretroviral therapies. The methodology proposed in this research was conducted through a qualitative analysis of the subject throught exploratory research. Using elements such as: a literature review, documentary research through newspapers, magazines and movies on the HIV/AIDS issues; and interviews with professionals who acted and act in the treatment of patients with HIV for further analysis of content. The results obtained from this research demonstrated the underspending of PNH as supportive tool to adherence of antiretroviral therapies in the researched county.